Lowering Regional Inflation? Improve Budget Absorption - Vid Adrison; Masarina Flukeria (Institute for Economic and Social Research, 2016)
The subnational government spending in Indonesia exhibit a highly skewed distribution, i.e., it is very low in the first two-quarters and then increases significantly in the last two-quarters. Such explosive pattern poses two disadvantages. First, the regional output will fall below its optimal level as the low government capital expenditure leads to a fewer provision of public goods. Second, a significant increase in government spending in the later quarter pushes the short run aggregate demand to the northeast and creates an inflationary pressure in the following quarters. In this study, we analyze the effect of quarterly regional government expenditure growth on regional inflation during 2010–2014. Using Arellano Bond GMM estimation, we find government expenditure growth leads to higher inflation in the same quarter. A percentage increase in non-capital expenditure spending results in a higher inflation than a percentage increase in capital spending.AbstrakPengeluaran pemerintah daerah di Indonesia menunjukkan distribusi yang sangat timpang, yaitu sangat rendah pada dua kuartal pertama dan kemudian meningkat secara significant pada dua kuartal terakhir. Pola eksplosif tersebut menimbulkan dua kerugian. Pertama, output regional akan berada di bawah tingkat yang optimal karena pengeluaran pembangunan (belanja kapital) pemerintah yang rendah akan mengakibatkan rendahnya barang publik yang tersedia. Kedua, peningkatan belanja pemerintah pada kuartal terakhir akan mengakibatkan kenaikan permintaan agregat dan mengakibatkan tekanan inflasi pada kuartal berikutnya. Dalam studi ini, kami menganalisa dampak dari pertumbuhan pengeluaran pemerintah daerah di Indonesia terhadap inflasi daerah periode 2010–2014. Dengan menggunakan estimasi GMM Arellano Bond, kami menemukan pertumbuhan pengeluaran pemerintah daerah akan mengakibatkan inflasi daerah pada kuartal yang sama. Satu persen peningkatan belanja non-kapital mengakibatkan inflasi yang lebih tinggi dibandingkan dengan satu persen peningkatan belanja kapital.Kata kunci: Belanja Kapital; Belanja Non-Kapital; Inflasi Daerah; Pemerintah DaerahJEL classifications: E31; H72